(untitled) (Research, Society and Development, 2020)
The objective of this work is to analyze the evolution of the regulation of oil exploration and trade in Brazil, which started with the approval of the Petroleum Law (1997), discussing how public and private ideas and interests interact with the institutions in force, as well as as with political actions and economic conditions, to generate a new configuration for the oil sector. This work also points to the historical determination of the agents’ choices, shows how economic conditions were decisive in the construction of the Brazilian economic policy around oil exploration, combined with the interests represented by multilateral institutions. Finally, it clarifies the importance of the volume of oil reserves in determining the new regulatory framework for oil and demonstrates the reason for the increase in Petrobras’ value and how such aspects may impact on Public Policies for social well-being. However, for methodological purposes, a narrative literature review was carried out, from April 2014 to January 2019, in two ways: access to the dissertation and thesis catalogs of the Bank of Theses of the Coordination for the Improvement of Higher Education Personnel (CAPES) ) and the Brazilian Digital Library of Theses and Dissertations (BDTD).